Numerical Analysis and Demonstration: Transmission Shaft Influence on Meshing Vibration in Driving and Driven Gears. (6th September 2015) - Jinli, Xu; Xingyi, Su; Bo, Peng
Abstract : The variable axial transmission system composed of universal joint transmission shafts and a gear pair has been applied in many engineering fields. In the design of a drive system, the dynamics of the gear pair have been studied in detail. However few have paid attention to the effect on the system modal characteristics of the gear pair, arising from the universal joint transmission shafts. This work establishes a torsional vibration mathematical model of the transmission shaft, driving gear, and driven gear based on lumped masses and the main reducer system assembly of a CDV (car-based delivery vehicle) car. The model is solved by the state space method. The influence of the angle between transmission shafts and intermediate support stiffness on the vibration and noise of the main reducer is obtained and verified experimentally. A reference for the main reducer and transmission shaft design and the allied parameter matching are provided.